Digital Archival Preservation and Cultural Heritage: A Practice-led Study and Preservation Project of the Work of late Sculptor Bonginkosi Michael Gasa (Journal of the Digital Humanities Association of Southern Africa, 2024)
This paper presents a current MA study that addresses the research problem, "What issues and insights about the role of digital archives in the preservation of South African cultural history are raised via the production of an archival documentary and archival website on the life and art of the late sculptor Mr. Bonginkosi Michael Gasa?". This study hopes to show, through the presentation of research and archival material curated thus far, not only the importance of the role archival documentary film and the digital platform play in the preservation of heritage but also how this archival project promotes the idea of an African gaze, which is essential for preserving an authentic cultural voice and heritage. This study is conducted by following a practice-led slant, meaning the research primarily leads to new information about the practice. In this case, the practice will investigate the key elements that go into the production of an archival documentary and secondly the digital archiving of the project online. Mr Bonginkosi Michael Gasa was a sculptor who passed away on the 18th of April 2019 at the age of 55. The film about Mr. Gasa will be reported in a critical reflexive MA dissertation, which will also serve to elucidate the critical, theoretical, and cultural matrix from which the film emerges. The documentary film will be preserved on a website, which will also serve as an online repository, curation, and record of Mr. Gasa’s sculptures. In detailing the study thus far, this paper aims to highlight the potential of digital archives to preserve marginalized voices, such as Michael Bonginkosi Gasa, whose life and work would otherwise remain largely unknown. Moreso, this paper and study hope to show that archives exist to be used for present and future generations, and in this way, to preserve our national heritage.